FACTORS INFLUENCING WORK ENGAGEMENT AMONG MALAYSIAN PUBLIC UNIVERSITY ACADEMICS: THE ROLES OF JOB DEMANDS-RESOURCES - Ibrahim, Siti Balkis Mohamed; Basir, Siti Norayu Mohd; Johanis, Mohd Arsad; Habib Sultan, Nor Hafizan; Nazri, Nazra Aliff (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
This study investigates the influence of personal resources, job resources (autonomy, social support, performance feedback), and job demands (workload, emotional demand) on work engagement among academic staff in Malaysian public universities. It contributes to the Job Demand-Resources (JD-R) model by incorporating Big Five personality traits as personal resources. Employing a cross-sectional quantitative design, data were collected from 132 academic respondents using a non-probability sampling method through an online questionnaire. Data analysis involved descriptive statistics, reliability testing, normality assessment, Pearson correlation, and multiple linear regression. Results indicate that personal resources and workload significantly predict work engagement, whereas autonomy, social support, performance feedback, and emotional demand do not. The findings suggest that enhancing motivational factors across multiple dimensions is essential to sustaining academic engagement and advancing the JD-R model’s applicability within higher education contexts.